A case of primary urethral lymphoma presenting as a huge mass surrounding the female urethra - Shimizu, Y (Hinyokika kiyo. Acta urologica Japonica, 1997)
A patient with a primary malignant lymphoma surrounding the female urethra is reported. Despite the good response of the primary tumor to radiotherapy, the patient died shortly after diagnosis due to disseminated disease. We reviewed 16 cases of this rare entity reported previously